(untitled) (Veterinary Science, 2018)
IL-1β, a proinflammatory cytokine, is involved in the conceptus implantation, invasion and fetal-maternal immunotolerance. It participates in the development of the trophoblast, communication with the endometrium and it´s necessary for a correct implantation. However, the presence of this cytokine, both at the placental and systemic levels, is unknown during the period after the implantation in swine, a species that has an epitheliocorial, noninvasive, adecidua, folded and diffuse placenta. In this study, the concentration of IL-1β in sera, uterus homogenates of non-pregnant sows and homogenates of maternal and fetal placenta of different gestational periods (30, 60, 70 and 114 days) were determined. A peak IL-1β tissue concentration was observed during gestation at 60-70 days in both maternal and fetal placenta. At the systemic level, the determination demonstrated an opposite pattern, a peak in serum IL-1β levels was observed at the end of gestation. These results suggest that IL-1β is useful between the 60 and 70 days of the gestational period in a tissue level, for participation in the molecular mechanisms that allows remodeling in the placental characteristic of this period. Furthermore, the increase of the serum cytokine at the end of gestation probably aims to activate the pro-inflammatory immune system for the onset of labor and expulsion of the placentas